2021
DOI: 10.24843/jiab.2021.v16.i01.p01
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and Consequences of Students Learning Satisfaction During Covid-19 Pandemic

Abstract: This study examines the effect of student perception in online learning on student satisfaction and its impact on student learning performance and intention to use in the future. The regression analysis method was used based on the survey results from 157 students. Results indicate that students' perceptions of online learning had a positive effect on student satisfaction, intention to use, and student learning performance. Further, student satisfaction has a positive effect on student learning performance but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
2
0
2
Order By: Relevance
“…Lekatnya masyarakat Jawa Tengah dan jamu pun mendorong kepopuleran konsumsinya di masa pandemi. Menurut penelitian Saragih and Saragih (2020) menyebutkan bahwa sebanyak 76% dari 200 responden dengan rentang usia 18-55 tahun cenderung membuat empon-empon atau yang disebut juga rempah-rempah sebagai minuman pada masa pandemi Covid-19. Penggunaan jamu, khususnya rempah-rempah dipercaya dapat meningkatkan dan menjaga daya tahan tubuh.…”
Section: Abstrakunclassified
See 1 more Smart Citation
“…Lekatnya masyarakat Jawa Tengah dan jamu pun mendorong kepopuleran konsumsinya di masa pandemi. Menurut penelitian Saragih and Saragih (2020) menyebutkan bahwa sebanyak 76% dari 200 responden dengan rentang usia 18-55 tahun cenderung membuat empon-empon atau yang disebut juga rempah-rempah sebagai minuman pada masa pandemi Covid-19. Penggunaan jamu, khususnya rempah-rempah dipercaya dapat meningkatkan dan menjaga daya tahan tubuh.…”
Section: Abstrakunclassified
“…Rempah-rempah yang biasanya digunakan untuk meracik jamu adalah jahe, temulawak, kunyit dan masih banyak lagi (Sumarni et al, 2019). Selanjutnya, jenis rempah yang paling banyak digunakan masyarakat Indonesia selama pandemi Covid-19 adalah jahe sebesar 44%, kemudian jeruk/lemon 25%, kunyit 10% dan lainnya 20.5% (Saragih and Saragih, 2020).…”
Section: Abstrakunclassified
“…As previously explained, the tax brevet is an informal tax education. On the other hand, such as the research conducted by Saragih et al, (2021) which examines online learning sys-tems based on formal education, it is found that students tend to choose to do face-to-face learning. This can be the basis of innovation for tax brevet organizers in the future.…”
Section: Hypothetical Testingmentioning
confidence: 99%
“…To address these challenges and enhance online learning success, it is essential to identify the factors that influence the effectiveness of online learning. The information system success (ISS) model has been widely used to study the success of online learning, examining factors such as technology system quality, information quality, service quality, support system quality, learner quality, teacher quality, and perceived usefulness [8][9][10]. However, most of these studies have focused on universities in developed countries.…”
Section: Introductionmentioning
confidence: 99%